MENGHADAPI TANTANGAN MENTAL HEALTH GEN Z MELALUI PENDEKATAN AYAT-AYAT Al-QURAN: INOVASI DALAM BIMBINGAN DAN KONSELING ISLAM - Putri Widia, Amanda; Sika Raemif Akbar; Muhammad Tisna Nugraha; Nur Hamzah (As-Sulthan Journal of Education, 2025)
Generation Z faces various mental health challenges such as anxiety, depression and stress. In this context, an Islamic guidance and counseling approach based on the Koran offers an innovative solution. This article discusses the application of Al-Quranic verses in addressing Gen Z mental health issues and proposes an effective Qur'anic approach for Islamic counselors in their practice. This approach shows significant potential in helping Gen Z deal with psychological distress through a strong spiritual foundation. This research method uses the literature review method. The research results show that the Qur'anic approach to Islamic guidance and counseling provides a holistic solution to the mental health challenges faced by Gen Z. By combining spiritual teachings from the Koran, such as tawakkul and tafakkur, with modern psychological methods such as CBT, Islamic counselors can offers comprehensive and balanced support between mental and spiritual aspects.